Nigeria - Consultations for Improved Primary Education - World Bank (Washington, DC, 2012)
The World Bank-assisted Nigeria Primary Education Project aims at assisting the Government of Nigeria to improve the quality of the subsector through the supply of instructional materials, upgrading of infrastructural facilities, enhancing teachers' competence, facilitating school management, inspection, planning and data gathering. This is being achieved by involving stakeholders at all levels in the process of primary school improvement. The National Primary Education Commission (NPEC) which manages a National Primary Education Fund and oversees the quality of primary education is responsible for implementing the project. In order to identify ways of improving primary education services and developing future policy, the NPEC decided to obtain the views of users and providers of current services and their suggestions for improvement by commissioning consultative surveys.